Varifocal versus monofocal LASIK in presbyopic hyperopic eyes - Taneri, Suphi; Kiessler, Saskia; Rost, Anika; Verma, Shwetabh; Arba-Mosquera, Samuel; Dick, H. Burkhard (Journal of refractive surgery, 2019)
Journal of Refractive Surgery | PURPOSE:To compare varifocal (SupraCor; Technolas Perfect Vision GmbH, Munich, Germany) to monofocal (Zyoptix TissueSaving; Bausch & Lomb, Rochester, NY) LASIK in patients with hyperopic presbyopia.METHODS:In this prospective, non-randomized, comparative case series, consecutive patients with hyperopia, presbyopia, and emmetropia as target refraction were bilaterally treated with varifocal (8
Gesehen am 17.04.2020